1984
DOI: 10.1128/jvi.52.1.88-93.1984
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple Epstein-Barr virus-induced nuclear antigens with sera from patients with rheumatoid arthritis

Abstract: By means of the protein immunoblot technique, the Epstein-Barr virus (EBV) nuclear antigen (EBNA) could be identified in a variety of EBV-transformed cell lines with anti-EBNA-positive sera from normal donors. The molecular weight of EBNA expressed in each of the cell lines varied between 70,000 and 75,000 and was dependent upon the strain of infecting virus. In contrast, 15 of 21 sera from patients with rheumatoid arthritis identified antigens in addition to EBNA. The most prominent of these antigens had mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…DNA from both lines was tested for the presence of genes coding for EBV. Whereas a strong band was obtained for an EBVtransformed cell line, QIMR B95-8 (Scully et al, 1984), neither PER-352 nor PER-364 gave any signal (data not shown).…”
Section: Characterization Of Cell Linesmentioning
confidence: 89%
“…DNA from both lines was tested for the presence of genes coding for EBV. Whereas a strong band was obtained for an EBVtransformed cell line, QIMR B95-8 (Scully et al, 1984), neither PER-352 nor PER-364 gave any signal (data not shown).…”
Section: Characterization Of Cell Linesmentioning
confidence: 89%
“…Preliminary experiments indicate that chemically induced Daudi virus also lacks transforming activity (B. Griffin, personal communication). Transforming recombinant virus between the P3HR-I and Raji viral genomes always contains the LT-1 region (Fresen et al, 1978;Skare et al, 1985). It is therefore of particular interest that both P3HR-1 and Daudi cells fail to express EBNA-2 (Dillner et al, 1 9 8 5~; Hennessy and Kieff, 1985).…”
mentioning
confidence: 99%
“…More recently, however, the presence of multiple EBV-specific nuclear antigens in EBV genomepositive cell lines was demonstrated, and most importantly, these antigens were identified with sera from RA patients (11). The most prominent of these additional antigens had a molecular weight of 92,000 daltons and has since been shown to correspond to EBNA-2 (Hennessy K: personal communication).…”
mentioning
confidence: 99%